Harnessing Artificial Intelligence for the Advancement of Mankind - Barnett, Patrick (Journal of Science & Technology, 2024)
The rapid progression of artificial intelligence (AI) over the past decade has ushered in an unprecedented era of technological advancement. From healthcare to environmental management, AI's transformative potential promises to address some of the most pressing challenges facing humanity. This paper explores the multifaceted applications of AI, emphasizing its capacity to drive innovation, enhance quality of life, and foster sustainable development.
Keywords: Artificial Intelligence; humanity